Anesthetic technique and postoperative pulmonary complications (PPC) after Video Assisted Thoracic (VATS) lobectomy: A retrospective observational cohort study. - Priyanka Singla; Brian Brenner; Siny Tsang; Nabil Elkassabany; Linda W Martin; Phillip Carrott; Christopher Scott; Michael Mazzeffi (PLoS ONE)
Introduction Thoracic surgery is associated with an 8-10% incidence of postoperative pulmonary complications (PPCs). Introduction of minimally invasive Video-assisted thoracoscopic surgery (VATS) aimed to reduce pain related and pulmonary complications. However, PPCs remain a common cause of morbidity after VATS. Methods The American College of Surgeons National Surgical Quality Improvement Program database was searched for VATS lobectomy cases from 2017 to 2021 with General Anesthesia (GA) as the primary anesthetic technique. Cases were stratified into four groups-GA alone, GA+local, GA+Regional and GA+Epidural. Generalized linear regression models were used to examine whether PPCs differ by anesthetic technique, controlling for morbidity risk factors. The study's primary outcome was the occurrence of any PPC (pneumonia, reintubation or prolonged mechanical ventilation). The secondary outcome was length of hospital stay (LOS). Results A total of 15,084 VATS lobectomy cases were identified and 14,477 cases met inclusion criteria. The PPC rate was between 3.5-5.2%. There was no statistically significant difference in the odds of PPCs across the groups. Compared to the GA alone group, the regional and local group had significantly shorter LOS (9.1% and 5.5%, respectively, both ps < .001), whereas the epidural group had significantly longer LOS (18%, p < .001). Conclusion Our analysis suggests that the addition of regional or local anesthesia is associated with shorter LOS after VATS lobectomy. However, these techniques were not associated with lower PPC incidence. Future randomized controlled trials could help to elucidate the best anesthetic technique to reduce pain and enhance recovery.